Effect of Textural Properties on the Adsorption and Desorption of Toluene on the Metal-Organic Frameworks HKUST-1 and MIL-101 - Feng Xu; Shikai Xian; Qibin Xia; Yingwei Li; Zhong Li (Adsorption Science & Technology)
The adsorption and desorption of toluene on metal-organic frameworks HKUST-1 and MIL-101 were studied. The adsorption isotherms and kinetic curves of toluene on HKUST-1 and MIL-101 were separately measured by gravimetric method. Temperature-programmed desorption experiments were carried out for estimating the interaction of toluene with the surfaces of HKUST-1 and MIL-101. Our experimental results showed that the isotherms of toluene on the adsorbents were well fitted by the Langmuir–Freundlich equation. The maximum amount of toluene adsorbed on MIL-101 was 15.1 mmol/g, which was much higher than that adsorbed on HKUST-1 (6.6 mmol/g). The high adsorption capacity of MIL-101 can be attributed to its higher surface area. However, the isotherm of toluene at P/P 0 < 0.09 on HKUST-1 was much higher than that on MIL-101 owing to the smaller pore size of HKUST-1. It is suggested that HKUST-1 had better adsorption performance than MIL-101 at low concentration of volatile organic compounds. The desorption activation energies, E d , of toluene on HKUST-1 and MIL-101 were 43.8 and 30.2 kJ/mol, respectively, meaning that the interaction of toluene with HKUST-1 was stronger than that with MIL-101. In addition, the diffusion coefficient of toluene within HKUST-1 was smaller than that within MIL-101. Results of thermal desorption experiments showed that the desorption efficiency of toluene from HKUST-1 and MIL-101 can separately reach above 93% and nearly 100% at 393 K, respectively.